Challenges to COVID-19 vaccine introduction in the Democratic Republic of the Congo – a commentary. Issue 6 (30th November 2022) - Zola Matuvanga, Trésor; Doshi, Reena H.; Muya, Albert; Cikomola, Aimé; Milabyo, Augustin; Nasaka, Pablito; Mitashi, Patrick; Muhindo-Mavoko, Hypolite; Ahuka, Steve; Nzaji, Michel; Hoff, Nicole A.; Perry, Robert; et al.
ABSTRACT: COVID-19 vaccination in the Democratic Republic of the Congo (DRC) began in April 2021. A month later, most COVID-19 vaccine doses were reallocated to other African countries, due to low vaccine uptake and the realization that the doses would expire before use. Based on data available on 13 August 2022, 2.76% of the DRC population had been fully vaccinated with last dose of primary series of COVID-19 vaccine, placing the country second to last in Africa and in the last five in global COVID-19 vaccination coverage. The DRC's reliance on vaccine donations requires continuous adaptation of the vaccine deployment plan to match incoming COVID-19 vaccines shipments. Challenges in planning vaccine deployments, vaccinating priority populations, coordinating, and implementing the communications plan, disbursing funds, and conducting supervision of vaccination activities have contributed to low COVID-19 vaccine coverage. In addition, the spread of rumors through social media and by various community and religious leaders resulted in high levels of vaccine hesitancy. A strong risk communication and community engagement plan, coupled with innovative efforts to target the highest-risk populations are critical to increase vaccine uptake during the next phase of COVID-19 vaccine introduction.